Optimizing Ship Berthing Allocation Strategies at a Dry Bulk Fertilizer Terminal: A Simulation Approach Considering Material Handling Equipment Availability - Putri, Maulin Masyito; Meilanitasari, Prita; Prasodjo, Nindya Putri; Arumjani, Dwi Sekar (Institute of Research and Community Outreach - Petra Christian University, 2025)
Long loading and unloading times at ports lead to demurrage costs, which occur when these activities exceed the agreed time. Demurrage is a penalty paid by shippers or charters to ship owners for delays. These delays can be caused by factors such as a lack of available docks or unprepared material handling equipment. This study examines dry bulk ports, focusing on four types of material handling, each with distinct characteristics and functions: the Continuous Ship Unloader (CSU) and Kangaroo Crane (KC) for unloading, and the Vessel Crane Flat Truck (VCFT), New Ship Unloader (NSL), and Vessel Crane with Dump Truck (VCDT) for loading. The CSU is the primary equipment for unloading, while the NSL is prioritized for loading bulk cargo. The variety of equipment and cargo adds complexity, best addressed through a discrete simulation approach. The study aims to identify the optimal berth allocation scenario, reducing loading and unloading times, waiting times, and demurrage costs using a discrete event simulation approach. Improvement scenario 2, which assigns berths based on the material being handled, resulted in a 33.49% increase in unloading revenue, a 1.81% increase in loading revenue, and a 13.54% reduction in demurrage costs.